Role of Freight Forwarder In Import Export Business At PT.Jasa Trans Samudera Sulut - LALOMA, VINNITA; Tampi, Johny R. E.; Mukuan, Danny D. S. (JURNAL ADMINISTRASI BISNIS, 2017)
Background This study was conducted at PT. Trans Samudera Sulut Service is one of the companies engaged in the service of the expedition which is usually called freight forwarder that serves the freight forwarder services in the form of cargo both domestically and abroad. The purpose of this research is to know how the role of freight forwarder in the implementation of import export business. The method of research used in this study is using data analysis that takes place along with data collection, such as data reduction, presentation and verification. In this research, Freight forwarder is a business entity that aims to provide services for all activities required for the implementation of the delivery, transport and receipt of goods by using multimodal transport either by land, sea or air. The role of freight forwarder in the import export business is the role in the consolidation of cargo, as the carrier, in the documentation, in the packaging, in insurance. Result of this research then the role of freight forwarder in the implementation of import export business has been done well although there may still be a few obstacles arises when import export activities take place as in the case of incompatibility between documents with checked goods, weather factor effects and shipping facilities that have not used own companies such as aircraft and ships. Therefore, companies should pay more attention to the roles of freight forwarders available at the time of export import. PT. Trans Samudera Sulut Services also contribute in providing services to assist some entrepreneurs from North Sulawesi who use their services to facilitate the delivery of goods either outside or outside the country. Keywords: Role of Freight Forwarder, Export and Import